Pendidikan Seni, Hubungannya dengan Ambang Sadar, Imajinasi dan Kreativitas serta Manfaatnya untuk Proses Belajar yang Bermutu - Primadi Tabrani (Wimba : Jurnal Komunikasi Visual, 2015)
It seems obvious that all theories of learning, teaching, training, and curriculum are borrowed from developed countries. However, from past and present experience, all of those theories will be less suitable for Indonesia. Therefore, we need the courage to study what happened in the West and compare the results with our own traditional education. Based on our own researches, then we can generate what is the present-day modern education of Indonesia.This article discusses about "inner-communication" "“ "image-communication" within our nerve system, where the awareness, imagination and creativity works. It is also a form of appeal to conduct research on education, especially on visual art education, so it will be suitable for Indonesian environment and society. Art education has the ability to increase the quality in other education fields, because the learning process transform into creation process.